Development of an Accelerated Model for ISPO Certification in Independent Palm Oil Plantations - Hadi, Syaiful; Kusumawaty, Yeni; Bakce, Djaimi; Yusri, Jum'atri (KnE Social Sciences, 2024)
The Indonesian government has committed to implementing sustainable palm oil plantation development. This commitment goes through some regulations that require smallholder plantations (plasma and independent) to have Indonesian Sustainable Palm Oil Certification (ISPO certified). Even though the ISPO certification obligation has been in effect since 2020, until mid-2023, there are still very few ISPO-certified smallholder oil palm plantations. This research aims to develop a model for accelerating ISPO certification for independent oil palm plantations as the largest part of smallholder oil palm plantations. The ISPO Certification acceleration model can be implemented by synergizing the Smallholders’ Palm Oil Rejuvenation Program (PSR) – ISPO program, which is coordinated from the central to provincial and district levels. This acceleration model can carry out three roles simultaneously, namely assisting PSR participants who are also ISPO certified, empowering large private plantations (PBS/large national plantations (PBN)) to contribute to the success of the PSR/ISPO program, and focusing more on helping farmers who are not yet included in the PSR program and PBS/PBN for ISPO certification. Keywords: model, ISPO certification, oil palm, independent smallholders